Environmental Landscape Management Guidelines Community Associations Can Use to Select a Landscaper and Write an Effective Landscaping Contract - Annemarie Post; Margaret D. Dessaint; Donald Rainey; Fred Santana (EDIS, 2008)
ENH-1080, a 15-page fact sheet by Annemarie Post, Margaret D. Dessaint, Donald Rainey, and Fred Santana, provides guidelines that community associations can use for selecting a landscape maintenance contractor and write an effective contract. Published by the UF Department of Environmental Horticulture, October 2007.